Factors associated with intelligence in young children with Down syndrome - Frieda Handayani Kawanto; Soedjatmiko Soedjatmiko; Aryono Hendarto (Paediatrica Indonesiana, 2012)
Introduction Despite the considerable number of children withDo\Vll syndrome in Indonesia, there is little data available on thesuccess of intervention programs. This study was performed todefine factors affecting the intelligence of young children withDo\Vll syndrome.Objective To determine factors associated Mth lower intelligencein children with Down syndrome, including growth parametersand participation in intervention programs.Methods This crossô€ƒsectional study was undertaken fromDecember 2010 to March 2011. Subjects were 60 childrenwith Down syndrome aged 2ô€ƒ6 years who were enrolled inan intervention program at both the Medical RehabilitationDepartment, Cipto Mangunkusumo Hospital, and the Growthand Development Clinic, Harapan Kita Women's and Children'sHospital. Parents' data was obtained through self historyô€ƒtakingand perusal of medical records. Subjects' anthropometricdata (body weight, body height, and head circumference) wasobtained through measurements using calibrated instruments.A psychologist administered IQ tests on the subjects. Results ofthe anthropometric and IQ tests were given to parents one weekfollowing the examinations.Results From the 111 children with Down syndromeregistered in the intervention programs, 60 children (36boys and 24 girls) met the inclusion criteria. The mean ageof subjects was 4 years 6 months. Most subjects were wellô€ƒnourished. Fiftyô€ƒfive subjects had microcephaly. Eightyô€ƒtwopercent of subjects participated in the program regularly and70% of subjects had started in the program at less than 1 yearof age. Subjects' mean IQ was 52.8. Analysis showed thatgirls, subjects who were overweight and obese, subjects withmicrocephaly, those with irregular attendance in the program,and those living under the poverty line were at highest riskfor severe mental retardation.Conclusion Factors associated v.ith the intelligence in childrenwith Down syndrome were female gender, overweight/obesity,Â severe microcephaly, belowô€ƒpoverty line economic status, andirregular participation in the program. [Paediatr Indones.2012;52:194-9].